RANCANG BANGUN TEMPAT SAMPAH OTOMATIS DENGAN PEMILAH SAMPAH ORGANIK DAN ANORGANIK DISERTAI NOTIFIKASI SMS BERBASIS ARDUINO - Santoso, Rudi Santoso; Qisti, Saiful; Subito, Mery; Sollu, Tan Suryani; Fauzi, Rizana; Ardias, Erwin (Foristek, 2023)
Garbage is a material left over from human activities which is an environmental issue and causes environmental pollution. Humans themselves are lazy to throw garbage in its place or are accustomed to littering, causing garbage to be scattered everywhere which in turn can cause garbage pollution, unpleasant odors and in the end can cause flooding. In this study, we will make a tool to sort organic and inorganic waste along with an Arduino-based SMS notification, namely by making a tool to sort out the types of organic waste and inorganic waste types which will later be classified separately and collected in their own place so that the waste is not mixed. To distinguish organic and inorganic waste using a capacitive proximity sensor as a separator of organic waste, an inductive proximity sensor as a separator of inorganic waste, arduino nano as a microcontroller to run all the work of the tool system. Servo motor as a sorting drive. GSM SIM 800l module as a sender of SMS notification of garbage that has been successfully sorted.